The Contribution of Nursing in the Prevention and Early Detection of Sepsis - Idelma Villalobos M (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
The purpose of the present work was to do a review on the "Surviving Sepsis Campaign" and to contribute to its diffusion in our environment, taking into consideration the necessary operability for its adaptation. From a revision of the medical and nursing journals, stands out the fact that, advances in the management of severe sepsis, the understanding of patho-physiology and new treatment strategies, have not reduced the sepsis mortality. In that sense, certain initiatives have been developed. One of which is the Sepsis Survival Campaign wich has divulged guidelines for severe sepsis and septic shock management. Nevertheless, it should be acknowledged that the main measure to undertake is that of prevention, for which nursing is best indicated as its professionals are in the best position to identify early signs due to the close relationship and continuous care of the patient.